Reproducing the humanities: Mevlana Rumi’s corpus in restructuring the study of man and society - Mohd Noor Merican, Ahmad Murad (IIUM Press, 2020)
The paper seeks to examine the corpus of Mevlana Jalaluddin Rumi (d. 1273) in light of establishing new ways of constituting the Human and Social Sciences. It is based on the assumptions that the existing social and human sciences are anthropocentric in nature, and were produced within a culture and civilization that placed man as the centre and the measure of things. That crucible which has become the origin for the production of knowledge operated within a chaotic West in the early modern and the modern periods. Thus, knowledge produced has been secular and disenchanted and sees man as a material object par excellence. As a result, modern man has lost his sense of origin, why he lives and whither he is going. The Infinite Wisdom to Man does not return to the Primordial, but develops a Faustian trajectory. This paper reattaches Rumi’s corpus to academic and intellectual levels as it informs daily life and consciousness. We need to reconsume the tenets of a ‘devolutionist’ History, Art, Sociology, Anthropology and Philosophy. It asks what the Mathnawi and the Fihi Mafihi can contribute to the Humanities from the Islamic perspective. How can they be used to restructure another mode of knowing? What disciplines can the Rumi corpus produce (or reproduce)? The significance of this paper is that it suggests a universalization, and thence, a deethnicization of the Social and Human Sciences, thus embracing the universal while mitigating the uniqueness of man in both his microcosmic and macrocosmic environments.